Effect of Magnesium ION (Mg2+) Substitution and Calcination to the Properties of Biphasic Calcium Phosphate (BCP) - Zahari, Mohamad Abdul Aziz (Universiti Sains Malaysia, 2018)
Magnesium-doped biphasic calcium phosphate (Mg-BCP) was successfully synthesized via aqueous precipitation method at room temperature. The objectives are to study the effect of substitution of magnesium ion and effect of calcination towards apatite structure. As-synthesized BCP powder was used as a reference in this research work. The as-synthesized Mg-BCP powder had been characterized via Thermogravimetry-Differential Scanning Calorimetry (TG-DSC), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The as-synthesized Mg-BCP powder was then fabricated by uniaxial pressing method to form a 13 mm diameter pellet and followed by calcination at three different temperatures (600 °C, 700 °C and 800 °C) in normal atmosphere. The Mg-BCP pellets had been characterized by XRD (phase), volume shrinkage, bulk density measurement, Vickers hardness test and FESEM (microstructure). The XRD result shows that only HA phase was formed for BCP pellets. However, for Mg-BCP pellets, HA and β-TCP mixture was successfully formed started at 700 °C. Thus, it is proved that the substitution of Mg2+ into BCP able to lower the β-TCP phase transformation temperature. Furthermore, by the formation of β-TCP, the hardness value of pellets dropped. Among the Mg-BCP pellets, the bulk density and hardness values obtained for C6 Mg-BCP(calcine at 600 °C) were 1.5534 g/cm3 and 43.8 HV, respectively and it showed that C6 Mg-BCP has better mechanical properties if compared to C7 Mg-BCP (calcine at 700 °C) and C8 Mg-BCP (calcine at 800°C). Therefore, the substitution of Mg2+ in apatite structure and increasing calcination temperature will reduce the hardness value of Mg-BCP pellets.